An Error Analysis Of Writing Of The First Semester Students Of English Education Department In Muhammadiyah University Of Surakarta In 2011/2012 Academic Year - Sari, Arina Puspita (2012)
This research paper is aimed at analyzing the types of errors in grammar in First Semester Writing class in Muhammadiyah University of Surakarta in 2011/2012 Academic Year. The background reason of conducting this research in this university is that the students are still lackof a sufficient writing skill, particularly on the grammatical usage and translation skill. In this research, the writer conducted descriptive qualitative method. It aims at collecting information of a phenomenon which occurred. The methods of collecting data are is documentation method. The technique of analyzing data are collecting the data from the documentation, analyzing the data, classifying the data, and concluding the result and giving suggestions. The results of the research paper show; 1) From 35 data of types of error, the most common types of errors made in writing by the students of first semester in Muhammadiyah University, English Education Department 2011/2012 academic year are omission error (10 data, 28,6%), addition error (7 data, 20%), regularization error (10 data, 28,6%), archi-forms (3 data, 8,6%), lternating-forms error (4 data, 11,4%), and misordering error (1 datum, 2,8%). And, From 30 data of problem of making error made in writing by the students of first semester in Muhammadiyah University, English Education Department 2011/2012 academic year are 17 data (56,7%) of translating from Indonesian to English, and 13 data (43,3%) of grammar.